The effectiveness of growth strategies used by Zimbabwean microfinance institutions to improve company performance - Mveku, Blessed; Mutero, Tanaka T. T.; Masinire, Sharon (Goodwood Publishing, 2024)
Purpose: Growth strategies are essential for the survival of MFIs worldwide; however, this phenomenon has not been extensively researched, particularly in developed countries. Accordingly, this study aims to ascertain the effectiveness of the growth strategies used by Zimbabwean microfinance institutions to improve company performance. Research Methodology: The study adopted a quantitative research approach using an explanatory research design. The target population was drawn from personnel at 10 registered microfinance institutions in Bulawayo, Zimbabwe, from accounting, finance, marketing, operations, and business development. The targeted population total was 250, and the sample size was 152, using Krejcie and Morgan's sample size determination model. The study employed a stratified sampling technique, and the data were analyzed using Spearman’s correlation coefficient. Results: Results showed that Digital innovation significantly affects the operational efficiency of MFIs. Funding diversification positively influences profitability. The results further show that an increased branch network positively affects the market share. Limitations: The current study's investigation of ten registered microfinance institutions within Bulawayo, Zimbabwe, restricts the generalizability of the findings to other contexts. Contributions: The findings of this study can influence policies and practices in Zimbabwe and other developing countries. The research will contribute massively to microfinance institutions, where they will be able to handle transactions, retain records, manage client databases, and enhance loan disbursement and repayment procedures.